Ecology of industrial pollution - Batty, Lesley C.; Hallberg, Kevin B. (Ecological reviews., 2010)
"Written for researchers and practitioners in environmental pollution, management and ecology, this interdisciplinary account explores the ecological issues associated with industrial pollution to provide a complete picture of this important environmental problem from cause to effect to solution. Bringing together diverse viewpoints from academia and environmental agencies and regulators, the contributors cover such topics as biological resources of mining areas, biomonitoring of freshwater and marine ecosystems and risk assessment of contaminated land in order to explore important questions such as: What are the effects of pollutants on functional ecology and ecosystems? Do current monitoring techniques accurately signal the extent of industrial pollution? Does existing policy provide a coherent and practicable approach? Case studies from throughout the world illustrate major themes and provide valuable insights into the positive and negative effects of industrial pollution, the provision of appropriate monitoring schemes and the design of remediation and restoration strategies."--NHBS Environment Bookstore.